The Characteristics and Expression Profile of Peptidoglycan Recognition Protein 2 in the Accessory Nidamental Gland of the Bigfin Reef Squid During Bacterial Colonization - Li, Hau-Wen; Kuo, Wei-Lun; Chen, Chi; Tseng, Yung-Che; Chang, Ching-Fong; Wu, Guan-Chung (Frontiers in Marine Science, 2022)
Some cephalopods carry microorganisms in two specialized organs, the light organ and the accessory nidamental gland (ANG). For the light organ, comprehensive mechanisms have been described for winnowing (bacterial selection) and maintenance of the symbiotic luminescent bacterium Vibrio fischeri (V. fischeri). However, the mechanisms controlling bacterial selection and maintenance during bacterial colonization of the ANG are open biological issues with physiological significance. Our recent study on bigfin reef squid (Sepioteuthis lessoniana) already showed that the ANG bacterial community shifts gradually and exhibits decreased diversity throughout maturation. This study further describes a potential role of an innate immunity-involved molecule, peptidoglycan recognition proteins (PGRPs), in the ANG of bigfin reef squid during bacterial transmission and colonization. First, we found that four homologs of the PGRP family are expressed in the ANG of bigfin reef squid (slPGRP2-5), but only slPgrp2 transcript levels are highly correlated with ANG development and bacterial colonization. Besides, slPgrp2 transcripts are mainly expressed in the epithelial cells of certain secondary tubules of ANG, and the expression levels are varied in the epithelial cells of other secondary tubules. This data reveals that slPgrp2 transcripts may associate with the composition of bacterial consortium and its secretary factors. Moreover, recombinant slPGRP2 had a negative effect of Escherichia coli (E.coli) which inhibited bacterial growth in culture. Therefore, our data suggest slPgrp2 expression in the epithelial cells of secondary tubules in the ANG may have an essential role in the winnowing and maintenance of holobiont homeostasis in bigfin reef squid.